Welcoming The Future: Challenges and Opportunities for Villagers in Lake Bermanei Tourism Development - Bunga Tri Kartini; Heni Nopianti; Diyas Widyarti (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
Lake Bermanei has undergone various changes since 2009, with the construction of concrete embankments, asphalt roads and art performances. However, it has not yet achieved tourism popularity equivalent to other tourist attractions. The research aims to analyze what are the challenges and opportunities for the community in developing the tourist attraction. Although many studies have been conducted on tourism development in various locations, specific research on the potential and challenges of tourism development in Lake Bermanei, especially in this context, has never been researched. Using a qualitative approach with data collection techniques through observation and interviews. The population used included all community members of Pahlawan Village as well as related parties such as local government and local communities. Samples were taken from representatives of the village community and local government officials. Data were analyzed using Max Weber's action theory, which focuses on the rational actions taken by the government and community in overcoming challenges and taking advantage of opportunities in tourism development by carrying out inauguration activities, and adding several playgrounds. The results showed that Lake Bermanei has the potential for tourism development with beautiful natural attractions, adequate facilities and infrastructure and the potential for economic improvement. However, it has challenges related to limited fund management, lack of knowledge and interest in community tourism, and limited utilization of technology for promotion. The implication of this research is the need for a planned strategy to overcome these challenges, such as increasing the capacity of fund management, training for the community, and utilizing information technology for tourismÂ promotion.Keywords: Challenges; opportunities; tourism development.